Illegal Secrets - Jenny-Brooke Condon (Washington University Law Review, 2014)
When can the government keep its illegal action secret? In spite of the strong incentive for government officials and institutions to hide unlawful conduct from the public and their demonstrated tendency to do so, both public information access doctrines and the broader normative discussion of government secrecy inadequately answer this question. The questionable legality and pervasive secrecy of recent national security activities—in particular, the National Security Agency’s (“NSA’s”) collection of millions of Americans’ phone records, the government’s unilateral and self-serving decision to characterize illegal conduct like torture as an “intelligence method” protected from public disclosure, and the government’s position that it can secretly kill suspected terrorists through unmanned drone strikes abroad without public oversight of the claimed legal authority to do so—underscore the extent to which democratic accountability is undermined when government secrecy and the prospect of illegality converge. This Article examines when the illegality (as well as the possible illegality) of executive action should preclude government attempts to keep its conduct secret. Or, to put it simply, it examines when a government secret becomes an illegal secret. In addressing the under-theorized relationship between secrecy and illegality with respect to government information control, this Article also examines the insufficiently acknowledged problem of shallow secrets that conceal illegal or potentially illegal government conduct. In recent years, the problem of illegal secrets has surfaced with increasing frequency and urgency. In a variety of Freedom of Information Act (“FOIA”) cases, when members of the public have sought information about controversial and legally suspect government policies and programs courts have largely deferred to the Executive’s claims that it is entitled to withhold information irrespective of whether the activities at issue violate the law. Indeed, numerous courts have expressly held that government illegality is irrelevant when evaluating the appropriateness of government secrecy decisions. Examining this troubling trend, this Article argues that the legality of secret government conduct is a vital consideration that must be prominent in an information disclosure regime premised upon the goal of democratic accountability. It therefore proposes that the established illegality of the underlying conduct sought to be exposed is a powerful basis for compelling disclosure of government information. Only in the most pressing and exceptional cases should executive claims of a national security priority present a paramount justification for withholding information from the public. This Article further posits that where there is a plausible allegation of illegality, courts must consider whether sanctioning government secrecy will thwart public debate regarding the lawfulness of the conduct concealed, such that the more plausible the allegation of illegality, the stronger the basis for disclosure.
Keywords: illegal; phone records; National Security Agency; intelligence; public disclosure; Freedom of Information Act; executive; disclosure